Controlling collagen gelation pH to enhance biochemical, structural, and biomechanical properties of tissue‐engineered menisci. Issue 4 (27th October 2022) - Kim, Jongkil; Bonassar, Lawrence J.
Abstract: Collagen‐based hydrogels have been widely used in biomedical applications due to their biocompatibility. Enhancing mechanical properties of collagen gels remains challenging while maintaining biocompatibility. Here, we demonstrate that gelation pH has profound effects on cellular activity, collagen fibril structure, and mechanical properties of the fibrochondrocyte‐seeded collagen gels in both short‐ and long‐terms. Acidic and basic gelation pH, below pH 7.0 and above 8.5, resulted in dramatic cell death. Gelation pH ranging from 7.0 to 8.5 showed a relatively high cell viability. Furthermore, physiologic gelation (pH 7.5) showed the greatest collagen deposition while glycosaminoglycan deposition appeared independent of gelation pH. Scanning electron microscopy showed that neutral and physiologic gelation pH, 7.0 and 7.5, exhibited well‐aligned collagen fibril structure on day 0 and enhanced collagen fibril structure with laterally joined fibrils on day 30. However, basic pH, 8.0 and 8.5, displayed a densely packed collagen fibril structure on day 0, which was also persistent on day 30. Initial equilibrium modulus increased with increasing gelation pH. Notably, after 30 days of culture, gelation pH of 7.5 and 8.0 showed the highest equilibrium modulus, reaching 150 –160 kPa. While controlling gelation pH is simply achieved compared with other strategies to improve mechanical properties, its influences on biochemical and biomechanical properties of the collagen gel are long‐lasting. As such, gelation pH is a useful means to modulate both biochemical and biomechanical properties of the collagen‐based hydrogels and can be utilized for diverse types of tissue engineering due to its simple application.